Effectiveness of CIPAA Implementation in Construction Industry from the Perspective of Contractors in Malaysia - Ahmi, Nur Nadia; Mohd Zainudin, Nurhaizan; Lee, Chia Kuang (GBMR, 2023)
Purpose: As an effort to reduce the default payment problems, the enactment of the Construction Industry Payment and Adjudication Act (CIPAA) 2012 was endorsed by the government and CIPAA is put into implementation in handling default payment problems. This paper aims to analyze contractors’ perception on the implementation of CIPAA in handling default payment issues and to examine contractors’ opinion on the effectiveness of the provisions set out in the CIPAA in solving payment issues among contractors Design/methodology/approach: A questionnaire survey was employed, and data were collected from 139 Class A contractors in Selangor. Findings: The result show that majority of the contractors support on the implementation of CIPAA and agree that CIPAA is an effective method in solving default payment issues. Apart from being an effective method, the findings also provide insights into how the implementation of CIPAA offers greater benefits to the contractors beside solving disputes over payment in projects. Research limitations/implications: The findings of this study are limited in the State of Selangor only. While most contracting companies and several megaprojects are in the Selangor state, the findings of this study cannot be used to generalize the population of the study. Practical implications: This study benefits several key players in the construction industry, namely the contractors, subcontractors, consultants, and project owners in solving payment issues. Originality/value: This study contributes to the understanding of perceived effectiveness in the implementation of CIPAA in solving payment issues, involving contractors in Malaysia. Keywords: CIPAA, Dispute Resolution Method, Payment Issues, Construction Industry, Effectiveness